2021
DOI: 10.3390/nano11113112
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Epitaxial Growth and Atomically Sharp Interface of Graphene/Ferromagnetic Heterostructure via Ambient Pressure Chemical Vapor Deposition

Abstract: The strong spin filtering effect can be produced by C-Ni atomic orbital hybridization in lattice-matched graphene/Ni (111) heterostructures, which provides an ideal platform to improve the tunnel magnetoresistance (TMR) of magnetic tunnel junctions (MTJs). However, large-area, high-quality graphene/ferromagnetic epitaxial interfaces are mainly limited by the single-crystal size of the Ni (111) substrate and well-oriented graphene domains. In this work, based on the preparation of a 2-inch single-crystal Ni (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The coverage of multilayer graphene (layers ≥3) increases from 77.7% on a 300 nm Ni substrate to 96.3% on a 600 nm Ni substrate using the image gray statistical approach. The coverage of multilayer graphene does not reach the theoretical prediction of 100% due to the actual complicated process of graphene growth, such as the reaction gas etching effect of graphene, nonideal dissolution, and segregation of carbon for the nonuniform layer. The different ways of the dissolution of carbon impurities in the Ni(111) film are implemented, as shown in Figure S3.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The coverage of multilayer graphene (layers ≥3) increases from 77.7% on a 300 nm Ni substrate to 96.3% on a 600 nm Ni substrate using the image gray statistical approach. The coverage of multilayer graphene does not reach the theoretical prediction of 100% due to the actual complicated process of graphene growth, such as the reaction gas etching effect of graphene, nonideal dissolution, and segregation of carbon for the nonuniform layer. The different ways of the dissolution of carbon impurities in the Ni(111) film are implemented, as shown in Figure S3.…”
Section: Resultsmentioning
confidence: 89%
“…The preparation and characterization of wafer-scale Ni(111) films were described detailed in our previous work. 30,31 The growth of multilayer graphene on Ni(111) film includes two steps. First, the dissolution of carbon impurities in a Ni(111) film was performed by CVD in an atmospheric tube furnace system.…”
Section: Methodsmentioning
confidence: 99%
“…The dominant angle of the peak at 22.7° and 37.3° is consistent with the same superlattice periodicity at angles θ and (60° – θ) of 6-fold symmetric graphene lattice. Iwasaki et al reported that the twist angle θ of bilayer graphene was related to the moiré superlattice periodicity . The twist angle θ = arccos .25em 3 i 2 + 3 i + 1 / 2 3 i 2 + 3 i + 1 and superlattice periodicity L = a 3 i 2 + 3 i + 1 , where a = 2.46 Å is the lattice parameter of graphene and i takes on the values 1, 2, 3, ...…”
Section: Resultsmentioning
confidence: 99%
“…Iwasaki et al reported that the twist angle θ of bilayer graphene was related to the moirésuperlattice periodicity. 42 The twist angle arccos…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation